Impact of a Textbook on the Learning of Spanish Literature: A Perspective from the University of Guyana (Docentes 2.0 Journal, 2024)
The absence of a specially adapted textbook for the course “Introduction to Spanish Literature” at the University of Guyana represented major challenges for students. This research aimed to assess the impact of the book “Brief Introduction to Spanish Literature” on learning Spanish literature at that educational institution. The study was based on the positivist paradigm, using the deductive method and quantitative approach with a longitudinal experimental design. The sample consisted of five students who took the course for two consecutive academic years. A Likert scale survey and an eight-question questionnaire were used. The results highlighted the positive perception of the book’s link to the course program and its contribution to learning Spanish literature. The study emphasized the relevance of textbook design for linguistic and literary learning, underlining the need to improve textbook design to foster linguistic competence and literary appreciation at the University of Guyana.
Keywords: Language learning; texts evaluation; Spanish literature; university perspective